Treatment of Notalgia Paresthetica with botulinum toxin A: a review - Bianca de Brito Tavares;; Camila Abreu Figueiredo; Julia Rodrigues Pontes; Juliana Messias Moraes Guapo; Marcele Lima Cunha; Sandra Lopes Mattos Dinato (Surgical & Cosmetic Dermatology, 2023)
Notalgia Paresthetica (NP) is a sensory neuropathy characterized by itching, with or without a macule. The Botulinum Toxin A treatment may have beneficial effects on pruritus, possibly by inhibiting the substance P. This study aims to evaluate the benefits/limitations of Botulinum Toxin in NP treatment. The methodology consisted of the selection of publications in PubMed, filtered by predefined criteria. Five articles were compiled, and the results were favorable in four of them. The study concluded the effectiveness of Botulinum Toxin A treatment in most of the articles, especially in the pruritus improvement.